Segregation behavior of binary mixtures of cylindrical particles with different length ratios in the rotating drum - Yang, Shiliang (2021)
Particle shape impacts the flow behavior of granular material but this effect is still far from being fully understood. Using discrete element method, the current work explores the segregation phenomena of the binary mixtures of cylindrical particles (differing in length but with the same diameter) in the three-dimensional rotating drum operating in the rolling regime, with each cylindrical particle fully represented by the superquadric equation. The important characteristics and the effect of length ratio on the flow dynamics of the binary mixtures are discussed. Some trends are in sync with those of binary mixtures of spherical particles. Unique to nonspherical particles is the orientation of particles, with results indicating that the cylindrical particles align their major axes perpendicular to the drum axis and this behavior becomes more significant for large particles when the length ratio increases. The length-induced radial segregation causes the orientation of large cylindrical particles to be less uniform.